1989
DOI: 10.1007/bf00017580
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an endochitinase cDNA clone from barley aleurone cells

Abstract: A barley aleurone cDNA library was screened using (32)P-labeled cDNA prepared by reverse transcription of mRNA from aleurone layers treated in the presence or absence of gibberellic acid (GA). Besides α-amylase cDNA clones, another set of clones representing an abundant mRNA in aleurone cells was identified. Messenger RNA hybrid-selected by a prototype clone of this group (clone 10) was translated in vitro to yield a 36 kDa protein. Analysis of the DNA sequence and the predicted amino acid sequence of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…We provide evidence that the selectivity in the heat shock-induced suppression of normal cellular protein synthesis is drawn upon the distinction of secretary versus nonsecretory proteins. Northern blot analysis demonstrated heat have extended our studies to mRNAs encoding a secreted thiol endoprotease ( 11) and an endochitinase (19). By Northern blot analysis it was apparent that the levels of protease mRNA were markedly increased by the presence of GA3 (Fig.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We provide evidence that the selectivity in the heat shock-induced suppression of normal cellular protein synthesis is drawn upon the distinction of secretary versus nonsecretory proteins. Northern blot analysis demonstrated heat have extended our studies to mRNAs encoding a secreted thiol endoprotease ( 11) and an endochitinase (19). By Northern blot analysis it was apparent that the levels of protease mRNA were markedly increased by the presence of GA3 (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Probes were made by nick-translating cloned cDNAs for the high-pI isozyme of a-amylase (pM/C) (14), the low-pI isozyme of a-amylase (clone E) (16), actin (pMAC-1) (17), endochitinase (19), protease (11), f3-tubulin (10), and three unidentified clones (nonGA3-inducible from barley aleurone layers) (L-S Lin, G Heck, T-hD Ho, unpublished data) in the presence of a-[32P]dCTP (New England Nuclear, specific activity >500 Ci/mmol).…”
Section: Rna Analysismentioning
confidence: 99%
“…Those CHs appear to be similar if not identical in tissue localization, amino acid sequence, and physical properties to CHs C and T, respectively (11,12 29) and cCHI26 (ref. 13), are derived from distinct genes, because the nucleotide sequences differ by 10% and their primary translation products differ in size.…”
Section: Discussionmentioning
confidence: 99%
“…During a previous study of genes expressed in the aleurone layer cells of germinating barley seeds, we identified a cDNA clone encoding a CH (29). Results of western blot analysis indicated the presence of at least two CHs in barley seeds.…”
mentioning
confidence: 99%
“…The primary structures and expression of various chitinases have been detennined in a variety of dicot and monocot plants (Swegle et al, 1989; Shinshi et al, 1990; Huang et al, 1991; Leah et al, 1991; Zhu and Lamb 1991; Huynh et al, 1992; Sela-Buurlage et al, 1993). These studies show that a11 stress-induced expression of chitinase activity is controlled by transcription rather than by enzyme activation, modification, or translation (Hedrick et al, 1988).…”
mentioning
confidence: 99%